Skeletal isomerization of heptanes over superacid catalysts of different nature - A. S. Berenblum; E. A. Katsman; V. Ya. Danyushevskiy; B. P. Krymov (Тонкие химические технологии)
The sequence of the formation of multi-branched heptane isomers was studied in liquid and gaseous phases over different liquid and solid superacid catalysts. It was found that this sequence does not depend on the phase state, catalyst nature, and conditions, evidencing in favor of common reaction mechanism. The 2,4-dimethylpentane transformation into 2,2-dimethylpentane can be explained by the intermediate formation of cyclobutyl carbocation.